Investigation of nonlinear dielectric properties in Sr0.75Ba0.25Nb2O6 relaxor ferroelectric thin films - Guerra, J. de los S.; Mendes, R. G.; Eiras, J. A.; Santos, I. A.; Araujo, E. B. [UNESP] (American Institute of Physics (AIP), 2008)
The ac and dc driving fields dependence of the dielectric permittivity for the strontium barium niobate relaxor ferroelectric thin films has been investigated. The nonlinear dielectric properties were obtained by using the measurements of the dielectric permittivity of the material as a function of the ac and dc "bias" electric field amplitude in wide frequency (100 Hz-10 MHz) and temperature (50-450 K) intervals. The results hint the existence of a true mesoscopic dielectric relaxor response in the ferroelectric thin film, which is very similar to those observed in bulk relaxor ferroelectrics. An anomalous behavior of the NL dielectric response was observed when submitted to moderate dc electric fields levels,,indicating a crossover from paraelectric to a glasslike behavior on cooling the sample toward the freezing transition. The obtained results were analyzed within the framework of the models proposed in the current literature.